Technical trading rules' profitability and dynamic risk premiums of cryptocurrency exchange rates - Khumbulani L. Masuku; Thabo J. Gopane (Journal of Capital Markets Studies (JCMS), 2022)
Purpose - The study considers time-varying risk premium in investigating the capability of technical analysis (TA) to predict and outperform a buy-hold strategy in Bitcoin exchange rate returns. Design/methodology/approach - The study tests the technical trading rule of fixed moving average (FMA) on daily actual and equilibrium returns of Bitcoin exchange rates. The equilibrium returns are computed using dynamic CAPM in conjunction with a VAR-MGARCH (1, 1) system. The empirical evaluation of the study uses a case study of four Bitcoin exchange rates (BTC/AUD, BTC/EUR, BTC/JPY and BTC/ZAR) for the period 19 June 2010 to 30 October 2020. Findings - The findings are consistent with related studies in conventional foreign exchange markets that find TA to be profitable, especially in emerging markets. Nevertheless, the consideration of risk premium has the effect of reducing the abnormal returns. Also, further robust tests reveal that Bitcoin returns possess a momentum effect which prompts further study in efficient market hypothesis research. Practical implications - The empirical findings of this study should benefit portfolio managers and active investors on the strength of TA to predict returns in a speculative market like the Bitcoin exchange rate market. Originality/value - The study takes cognisance that cryptocurrency trading is speculative in nature which renders it a good candidate for TA methods. While there are studies that have explored the value of TA in Bitcoin exchange rates, these studies fail to incorporate the effects of time-varying risk premiums, the strength and focus of the current paper.
Keywords: 330; Bitcoin; Cryptocurrency; Efficient market hypothesis; Fixed moving averages; Profitability; Technical analysis